Mixed glandular-neuroendocrine cancer of the gallbladder. Report of a case - Durczyński, Adam; Szymański, Dariusz; Sporny, Stanisław; Strzelczyk, Janusz (Contemporary Oncology/Współczesna Onkologia, 2011)
Here we present a unique case report of development of mixed glandular-neuroendocrine cancer four years after complete resection of advanced adenocarcinoma of the gallbladder in a 72-year-old woman. Primary treatment consisted of extended cholecystectomy with wedge resection of the gallbladder bed including more than 2 cm of normal liver and dissection of the regional lymph nodes. Recurrent tumour was treated by extended right hemihepatectomy and adjuvant chemotherapy. This case is the first description of mixed glandular-neuroendocrine cancer of the gallbladder and represents the long-term follow-up of a surviving patient with this stage of the disease. The authors discuss possible explanations of such a phenomenon and emphasize the need for evaluation of neuroendocrine differentiation in gallbladder carcinomas, which can be misdiagnosed, as it may be related to better prognosis, and may indicate the necessity of adjuvant chemotherapy application.